Thabo Mbeki and the Battle for the Soul of the ANC. - Gumede, William Mervin (Zed Books Ltd., 2007)
As a spokesman for a country, a continent and the developing world, Thabo Mbeki plays a crucial role in world politics, but to many people he is an enigma. This book explores the complex position that Mbeki occupies, following in Nelson Mandela's footsteps, heading a party with roots as a liberation movement, and ruling a divided country.